PROSPECTS FOR THE DEVELOPMENT OF BRAIN CYTOLOGICAL EXAMINATION IN PNEUMOCONIOSIS IN MINERS - Олег Иванович Бондарев; Сергей Николаевич Филимонов (Медицина в Кузбассе, 2023)
Coal industry workers are characterized by a high level of occupational diseases, including pneumoconiosis. The current level of diagnosis is based on clinical research methods, which often do not determine early changes in the lungs. Knowledge in the field of studying pneumoconiosis contains many contradictions in the diagnostic assessment of lung damage, in particular changes in the respiratory system at the initial stage of the disease without clinical manifestations. The study is devoted to early cytological examination of miners working in underground conditions. The task is to identify early morphological manifestations of dust pathology in miners, based on cytological research.